Investigation into the Influence of Polishing Depth and Speed on the Nano-Polishing Process of Nickel–Phosphorus Alloys via Molecular Dynamics - Jiadai Xue; Yutao Liu; Qiuyan Liao; Ziteng Li; Fei Ding; Yuan Jin; Duo Li; Yanwen Liu; Chuanrui Zhu; Yangong Wu; Bo Wang (Micromachines)
Nickel–phosphorus (NiP) alloys have been widely used in many engineering fields such as aerospace, automotive, and optics; however, it is difficult to study the material removal mechanism and microscopic size changes in the polishing process of nickel–phosphorus alloys through simple experiments. In light of these difficulties, there is a need to improve our understanding of the surface friction and wear mechanisms of NiP materials. In the present study, molecular dynamics simulations are employed for the first time to investigate the material removal mechanism, mechanical response, phase transformation, and stress distribution of two NiP alloys with different phosphorus contents during the nano-polishing process by adjusting the polishing depth and speed. Our simulation results indicate that the mechanical response of the low-phosphorus alloy is slightly higher than that of the high-phosphorus NiP alloy. Larger polishing depths and higher speeds reduce the surface quality and lead to increased residual stress. The findings presented herein provide an atomic-level understanding of the material removal mechanism of NiP alloys via MD methodology and offer valuable guidance for selecting alloys with an appropriate NiP ratio as engineering materials and for developing processing methods to improve surface quality.